Reconstructing Greenland Ice Sheet meltwater discharge through the Watson River (1949-2017) - van As, Dirk; Hasholt, Bent; Ahlstrom, Andreas P.; Box, Jason E.; Cappelen, John; Colgan, William; Fausto, Robert S.; Mernild, Sebastian H.; Mikkelsen, Andreas Bech; Noel, Brice P. Y.; Petersen, Dorthe; van den Broeke, Michiel R. (My University, 2018)
Ice-sheet melting is the primary water source for the proglacial Watson River in southern west Greenland. Discharge from the large, approximately 12,000 km(2) ice-sheet catchment draining through the Watson River has been monitored since 2006. While this record is of respectable length for a Greenland monitoring effort, it is too short to resolve climate signals. Therefore, we use observed Tasersiaq lake discharge and Kangerlussuaq air temperature to reconstruct annual Watson River discharge back to 1949. The resulting sixty-five-year record shows that average ice-sheet runoff since 2003 has roughly increased by 46 percent relative to the 1949-2002 period. The time series suggests that the five top-ranking discharge years occurred since 2003. The three top-ranking discharge years (2010, 2012, and 2016) are characterized by melt seasons that were both long and intense. Interannual variability more than doubled since 2003, which we speculate to be because of hypsometric runoff amplification enhanced by albedo decrease and decreased firn permeability. The reconstructed time series proves to be a valuable tool for long-term evaluation of Greenland Ice Sheet surface mass balance models. A comparison with freshwater fluxes calculated by a downscaled version of the regional climate model RACMO2 reveals high correlation (r = 0.89), and also shows that the model possibly underestimates runoff by up to 26 percent in above-average melt years.
Keywords: greenland ice sheet; melt; climate change; measurements; model validation; kangerlussuaq